Development of fatigue test technology of sheet automobile materials - Pachurin, German; Goncharova, Diana; Filippov, Alexey; Shevchenko, Sofia; Mukhina, Mariia; Kuzmin, Nikolay; Pachurin, Viktor; Matveyev, Yury; Kutepova, Lubov; Smirnova, Zhanna (Eastern-European Journal of Enterprise Technologies, 2018)
Ensuring the operability of the cars’ parts and components is one of the most topical problems in the modern automotive industry. Most of the car parts are under cyclic loads leading to materials’ destruction. Therefore, one of the important factors affecting the performance of products is the fatigue strength of the material. In this paper, the existing methods of fatigue tests are analyzed, their advantages and disadvantages are presented. The methodology of fatigue tests of sheet automobile materials was developed. The main idea of this methodology is that it enables to study the fatigue of sheet automobile materials based on single-plane pure bending. This scheme is very close to the conditions of the actual load of car body structural elements. The results of the study of fatigue strength obtained using this methodology allow studying the kinetics of the failure process, fixing the beginning of macrofailure, crack growth rate and, as a consequence, maintainability of the structure. Comparative tests enable to determine the material that best meets the operating requirements and provides the reduction of the failure rate of the car metal structures. In this paper, important characteristics of fatigue strength were obtained for a number of automobile structural steels 08kp and 20kp: service life to complete failure, fatigue limit, period to fatigue crack nucleation and rate of further propagation and, as a consequence, maintainability of the structure. So, for example, the number of cycles for 08kp steel to complete failure (262,000 cycles) and the period to fatigue crack nucleation (82,000 cycles) is greater, and the rate of further growth (5.38.10-5 mm/cycle) is lower than for 20kp steel (174,000, 68,000 cycles and 8.86.10-5 mm/cycle, correspondingly). Although these parameters were obtained at higher stress (265 MPa) for 08kp steel against only 235 MPa for 20kp steel. This explains the operating advantage of 08kp steel against 20kp steel in the process of car design. The obtained data enable to prevent failure of structural elements and parts under cyclic loads at the stage of car maintenance, and as a consequence, to increase the car operation safety, and to reduce the cost of repair